Hill on a mountaintop: A longitudinal and cross-sectional analysis of the relative age effect in competitive youth football. Issue 11 (17th June 2020) - Jackson, Robin C.; Comber, Gavin
ABSTRACT: The aim of this study was to examine the origin and persistence of the relative age effect (RAE) in competitive youth football. To examine its origin, birthdates of 121 category one Premier League academy players recruited over 6 years were compared with 691 Under 8 (U8) players in one of the regional grassroots leagues from which academy players are selected. To examine the persistence of the RAE we conducted a longitudinal comparison of retention rates in early-birth and late-birth academy players from U9 to U15, and made a cross-sectional comparison of birthdate distributions from U7 to U18 in 10, 857 regional league players. The results revealed birthdate asymmetry in both the academy and grassroots players but a much larger RAE in the academy. Longitudinal analysis revealed that the cumulative probability of retention at the academy was higher for early-birth than late-birth players. A small to medium RAE persisted across grassroots football age groups though it declined somewhat from U15 to U18. The implication of these results for academy player recruitment is discussed.